Guest Editorial: Special Issue on New Advances in Deep-Transfer Learning - Deng, Z.; Lu, J.; Wu, D.; Choi, K.-S.; Sun, S.; Nojima, Y. (IEEE transactions on emerging topics in computational intelligence, 2019)
The papers in this special issue aim to present the most recent advances in deep transfer learning (DTL). While deep learning has achieved great success in big data applications, transfer learning (TL) is an important paradigm mainly for small/insufficient data applications, which utilizes the data/knowledge in one task to facilitate the learning in another relevant task. How to integrate DL and TL to combine their advantages is an interesting and important research topic. DTL is proposed to address this issue. Deep learning extracts knowledge from big data, which can then be used by TL for a new task/domain with small/insufficient data.